Application of Hematopoietic Cells to Therapeutic Angiogenesis - Tateno, Kaoru; Minamino, Tohru; Miyauchi, Hideyuki; Kunieda, Takeshige; Komuro, Issei (Current Pharmaceutical Design, 2006)
Despite considerable progress in the field of cardiovascular medicine and surgery, ischemic heart disease is still the leading cause of death in advanced countries. In this context, it is no wonder why therapeutic angiogenesis, a way to ameliorate ischemic tissue from suffering dysfunction by increasing new blood vessels, gains so much attention from both clinicians and patients. In this review, we will briefly go through a decade of history in therapeutic angiogenesis including unraveling of its mechanisms, results obtained from clinical trials, and lessons learned from earlier investigations. We will then focus on an emerging, yet rapidly evolving field of hematopoietic cell therapy. Recent excellent studies seem to have brought us to the place where we might save so many patients from burden of ischemia, we should be aware that there are some controversies, and sometimes misunderstandings, regarding how or why this treatment does actually work, and what better way should we explore in order to get the best of its efficacy. With these caveats in mind, we will investigate the works elucidating the mechanisms and clinical efficacies of hematopoietic cell therapy.
Keywords: Therapeutic angiogenesis